Publisher Correction: The NORAD lncRNA assembles a topoisomerase complex critical for genome stability. (29th November 2018) - Munschauer, Mathias; Nguyen, Celina; Sirokman, Klara; Hartigan, Christina; Hogstrom, Larson; Engreitz, Jesse; Ulirsch, Jacob; Fulco, Charles; Subramanian, Vidya; Chen, Jenny; Schenone, Monica; Guttman, Mitchell; et al.
A typo in the 'Reviewer information' section of this Letter was corrected online.